Electrocatalytic oxygen evolution reaction on iridium oxide model film catalysts: Influence of oxide type and catalyst substrate interactions - Reier, T.; Weidinger, Inez M.; Hildebrandt, Peter; Kraehnert, Ralph; Strasser, Peter (ECS Transactions, 2013)
Different iridium oxides and their interactions with a titanium substrate were investigated with regard to their electrocatalytic oxygen evolution activities. Smooth iridium oxide thin-film model catalysts were synthesized at different temperatures. Thin-film catalysts minimize mass transport limitations, which tend to impede catalytic studies. Prior to the electrocatalytic investigation, the iridium oxide films were characterized by SEM, EDX, XRD, Raman spectroscopy and cyclic voltammetry. Temperature programmed reduction was applied to identify the oxide species formed as function of the calcination temperature. The TPR study was performed on inert silicon and titanium substrates to study iridium oxide properties alone and their interaction with the titanium substrate. Thus, it was possible to relate electrocatalytic oxygen evolution activity with the formation of the various oxide species. © The Electrochemical Society.
CRIS-Team Scopus Importer:2023-03-20